Systems and mechanisms to develop migrant health volunteers to improve the migrant workforce health: a case study in Samut Sakhon Province, Thailand - Suvarnathong, Preecha; Chai-Aroon, Teeradej; Jiawiwatkul, Uthaithip; Intoo-Marn, Pasakorn (Humanities, Arts and Social Sciences Studies, 2022)
The study aimed to investigate the systems and mechanisms to develop migrant health volunteers (MHVs) to improve the health of the immigrant workforce in Samut Sakhon Province. This qualitative study obtained data from document research, in-depth interviews with 13 participants including personnel working on MHVs development in public health organizations, nongovernmental organizations (NGOs) and MHVs. Data were collected from May to October 2017. Our results showed the development of MHVs originated from health problems caused by large flows of migrant workers into the province. This situation prompted NGOs in Samut Sakhon Province to seek translators and MHVs for projects. Later, public health organizations led by the Samut Sakhon Provincial Public Health Office became aware of how MHVs mattered to the health system. Being grounded in primary health care, MHVs had four systems to ensure development. These systems included volunteer selection, training and knowledge management, welfare management and budget support. By driving development through the committee under the mechanisms of the Provincial Public Health Office with NGOs and network partners. In fact, MHV development is subject to Provincial Public Health Office authorities. The findings and knowledge gained from this study would be applied to establish systems and mechanisms at provincial level to develop health volunteers and improve the migrant workforce health. The Provincial Public Health Office and concerned NGOs can employ their contexts to benefit all stakeholders in health volunteer development for immigrant health.